2010
DOI: 10.1007/jhep02(2010)084
|View full text |Cite
|
Sign up to set email alerts
|

Jet trimming

Abstract: Initial state radiation, multiple interactions, and event pileup can contaminate jets and degrade event reconstruction. Here we introduce a procedure, jet trimming, designed to mitigate these sources of contamination in jets initiated by light partons. This procedure is complimentary to existing methods developed for boosted heavy particles. We find that jet trimming can achieve significant improvements in event reconstruction, especially at high energy/luminosity hadron colliders like the LHC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
558
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 580 publications
(567 citation statements)
references
References 29 publications
1
558
0
1
Order By: Relevance
“…through the use of a set of jet reconstruction and identi cation methods that exploit the internal structure of jets, known as jet substructure techniques [73]. The Higgs boson candidate is reconstructed as a single anti − k T R = 1.0 jet, trimmed with subjet radius parameter R sub = 0.3 and subjet transverse momentum fraction p Ti /p jet T < 0.05, where p Ti is the transverse momentum of the i-th subjet and p jet T is the p T of the untrimmed jet [74]. This R = 1.0 jet must be associated with two b-tagged anti − k T R = 0.3 jets reconstructed only from charged particle tracks (track-jets) [75].…”
Section: Eft Modelsmentioning
confidence: 99%
“…through the use of a set of jet reconstruction and identi cation methods that exploit the internal structure of jets, known as jet substructure techniques [73]. The Higgs boson candidate is reconstructed as a single anti − k T R = 1.0 jet, trimmed with subjet radius parameter R sub = 0.3 and subjet transverse momentum fraction p Ti /p jet T < 0.05, where p Ti is the transverse momentum of the i-th subjet and p jet T is the p T of the untrimmed jet [74]. This R = 1.0 jet must be associated with two b-tagged anti − k T R = 0.3 jets reconstructed only from charged particle tracks (track-jets) [75].…”
Section: Eft Modelsmentioning
confidence: 99%
“…To reduce the impact of soft radiation and pileup, the large-radius jets are groomed using reclustered jet trimming, where constituents with p T less than 5% of the ungroomed jet p T are removed [111][112][113][114]. Electrons and muons are not included in the reclustering, since it was found that including them increases the background acceptance more than the signal efficiency.…”
Section: Event Reconstruction and Selectionmentioning
confidence: 99%
“…Large-radius jets have trimming [18] applied. Trimming allows the mitigation of pile-up in large-radius jets.…”
Section: Object Selectionmentioning
confidence: 99%